“They would like to move the language backwards, but the language can’t be moved back” – Attitudes toward the language ideological debates in Croatia - Skelin Horvat, Anita (2010)
The paper discusses various language attitudes towards some (puristic)trends in the Croatian language which try to introduce a number of old words and expressions instead of internationalisms.